THE NEW GALAXY SAMPLE FROM SDSS DR9 AT 0.003 ≤ Z ≤ 0.1 - Dobrycheva, D. V. (Одеські астрономічні публікації, 2013)
To test the relationships between morphological types of galaxies in pairs/groups and their physical properties (luminosity, mass, color index, the radial velocity, the inverse concentration index, the absolute magnitude, the radius of the de Vaucouleurs or scale radius, etc.) on a larger sample of the local Universe, we need the more representative data. With this aim we processed and prepared a sample of galaxies with 0.003 ≤ z ≤ 0.1 based on the latest SDSS DR9. The initial sample was about 724,000 objects and, consequently, 407,000 galaxy images after the preliminary processing. Because of the large number of duplicate and faulty images, we checked its carefully and obtained finally about 260,000 galaxies in the studied sample at z < 0.1. We discuss this procedure and properties of the studied galaxy sample.